Direct Application of Rep‐PCR on Type I Sourdough Matrix to Monitor the Dominance and Persistence of a Lactobacillus plantarum Starter Throughout Back‐Slopping. Issue 8 (11th July 2017) - Dolci, Paola; Cocolin, Luca
Abstract: This study describes the optimization and application of repetitive element‐PCR (rep‐PCR) technique directly on microbial DNA extracted from type I sourdoughs for fast monitoring of a Lb. plantarum starter strain (P1FMC) throughout daily back‐slopping. The challenge was to follow and study the performance of a starter culture directly in sourdoughs without cultivation on selective media. The extraction of good quality microbial DNA suitable for amplification from a complex matrix such as dough was the first target. In addition, the objective to obtain a clear rep‐PCR profile referable to a specific starter strain among a microbial community was pursued. Co‐inoculum trials, in flour matrix, with Lb. plantarum P1FMC and L. lactis LC71 strains and, subsequently, type I sourdough back‐slopping trials were performed. The rep‐PCR amplification profiles obtained were clearly referable to that of Lb. plantarum P1FMC starter in both co‐inoculum trials (also when it was present with one order of magnitude less with respect to L. lactis LC71) and back‐slopping trials where it dominated the fermentation process with loads of 10 8 cfu g −1 and prevailed on the autochthonous microbiota. Thus, the approach proposed in this paper could be considered a methodological advancement, based on a culture‐independent one‐step rep‐PCR, suitable for fast monitoring of starter performance.